High-detectivity ultraviolet photodetectors based on laterally mesoporous GaN - Liu, Lei; Yang, Chao; Patanè, Amalia; Yu, Zhiguo; Yan, Faguang; Wang, Kaiyou; Lu, Hongxi; Li, Jinmin; Zhao, Lixia (Royal Society of Chemistry, 2017)
Photodetectors for the ultraviolet (UV) range of the electromagnetic spectrum are in great demand for several technologies, but require the development of novel device structures and materials. Here we report on the high detectivity of UV photodetectors based on well-ordered laterally mesoporous GaN. The specific detectivity of our devices under UV-illumination reaches values of up to 5.3×1014 Jones. We attribute this high specific detectivity to the properties of the mesoporous GaN/metal contact interface: the trapping of photo-generated holes at the interface lowers the Schottky barrier height thus causing a large internal gain. The high detectivity along with the simple fabrication process make these laterally mesoporous GaN photodetectors of great potential for applications that require selective detection of weak optical signals in the UV range.